Wound healing and the antimicrobial impact by using biosynthesized iron oxide nanoparticles - Ibrahim, Abdulrahman K.; Al Sahlanee, Rasha (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Chronic wound infections are a major cause of chronic wound development. This study aimed to investigate the role of Fe2O3 nanoparticles (Fe2O3 NPs) in the growth inhibition of multidrug resistant bacteria (MDR) and enhancement of human foreskin cell line migration and proliferation. For this aim, Fe2O3 NPs were synthesized from the bacterial extract and characterized it with UV-Vis, EDS, FTIR, AFM and FESEM assays. In addition, investigate the antibacterial effect using the well diffusion method. as well as study the cytotoxicity effect via MTT assay and the migration of cells through the scratch wound assay for human foreskin (HFF) cell line. The results confirmed the synthesis of Fe2O3 as the UV-Vis, which showed a peak at 288 nm; EDS showed peaks that corresponded to that of Fe2O3 NPs; FTIR showed absorption of functional groups belonging to bacterial extract, while FESEM revealed the irregular agglomerated shape, and AFM showed a mean diameter of 84.45 nm for Fe2O3 NPs. The green synthesized Fe2O3 revealed an antibacterial activity on MDR bacteria (Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus). Moreover, a significant increase in the viability of HFF cell line in dose dependent manner leading to the enhancement of these cells to migrate and proliferate to close the scratched line in 12h of incubation under the effect of these NPs. In conclusion, the findings of the current study exhibited a successful synthesized nanoparticles Fe2O3 from bacterial extract. These NPs presented a significant antibacterial impact against MDR bacteria. Most importantly, they showed a significant biocompatibility and promoted cell viability, migration and proliferation in HFF cells. These findings point up the capability of Fe2O3 as a promising treatment for wound healing applications.